Sociodemographic and psychological predictors of intention to receive a COVID-19 vaccine in elderly peruvians - Caycho-Rodríguez, Tomás (2022)
The implementation of a vaccine against COVID-19 is one of the most important health strategies to mitigate the spread of the disease. The objective of this study was to estimate the prevalence of the intention to be vaccinated against COVID-19 and its predictors in older Peruvian adults. This is a cross-sectional study, where information was collected through an online survey regarding vaccination intention of the participants, as well as sociodemographic and psychological variables. A multiple regression analysis was applied to identify predictors of intention to be vaccinated against COVID-19. We evaluated 245 participants, who had a mean age of 72.74 years old (SD = 6.66). 65.5% of these older adults expressed a high likelihood of accepting vaccination, while 20.9% expressed a low likelihood of accepting vaccination, and 13.6% were hesitant. Eleven predictors were identified that explained 66.69% of the intention to vaccinate against COVID-19. This identified place of residence, perceived likelihood of contracting COVID-19, severity of previous infection with COVID-19, fear of the disease, previous refusal of a vaccine, concerns about vaccine sales and speculation, and trust toward vaccines against COVID-19, as the main predictors. Our results show that confidence in vaccines and previous vaccine refusal are relevant predictors of intention to vaccinate against COVID-19 in older adults; these findings may be useful to guide the development of campaigns for the immunization of this vulnerable group in the current pandemic. © 2021, Associação Brasileira de Psicologia.